In situ vaccination at a peripheral tumor site augments response against melanoma brain metastases. Issue 2 (19th July 2020) - Clark, Paul A; Sriramaneni, Raghava N; Jin, Won Jong; Jagodinsky, Justin C; Bates, Amber M; Jaquish, Abigail A; Anderson, Bryce R; Le, Trang; Lubin, Jonathan A; Chakravarty, Ishan; Arthur, Ian S; Heinze, Clinton M; et al.
Abstract : Background: Immune checkpoint inhibition (ICI) alone is not efficacious for a large number of patients with melanoma brain metastases. We previously established an in situ vaccination (ISV) regimen combining radiation and immunocytokine to enhance response to ICIs. Here, we tested whether ISV inhibits the development of brain metastases in a murine melanoma model. Methods: B78 (GD2 + ) melanoma 'primary' tumors were engrafted on the right flank of C57BL/6 mice. After 3–4 weeks, primary tumors were treated with ISV (radiation (12 Gy, day 1), α-GD2 immunocytokine (hu14.18-IL2, days 6–10)) and ICI (α-CTLA-4, days 3, 6, 9). Complete response (CR) was defined as no residual tumor observed at treatment day 90. Mice with CR were tested for immune memory by re-engraftment with B78 in the left flank and then the brain. To test ISV efficacy against metastases, tumors were also engrafted in the left flank and brain of previously untreated mice. Tumors were analyzed by quantitative reverse transcription-PCR, immunohistochemistry, flow cytometry and multiplex cytokine assay. Results: ISV+α-CTLA-4 resulted in immune memory and rejection of B78 engraftment in the brain in 11 of 12 mice. When B78 was engrafted in brain prior to treatment, ISV+α-CTLA-4 increased survival compared with ICI alone. ISV+α-CTLA-4 eradicated left flank tumors but did not elicit CR at brain sites when tumor cells were engrafted in brain prior to ISV. ISV+α-CTLA-4 increased CD8 + and CD4 + T cells in flank and brain tumors compared with untreated mice. Among ISV + α-CTLA-4 treated mice, left flank tumors showed increased CD8 + infiltration and CD8 + :FOXP3 + ratio compared with brain tumors. Flank and brain tumors showed minimal differences in expression of immune checkpoint receptors/ligands or Mhc-1 . Cytokine productions were similar in left flank and brain tumors in untreated mice. Following ISV+α-CTLA-4, production of immune-stimulatory cytokines was greater in left flank compared with brain tumor grafts. Conclusion: ISV augmented response to ICIs in murine melanoma at brain and extracranial tumor sites. Although baseline tumor-immune microenvironments were similar at brain and extracranial tumor sites, response to ISV+α-CTLA-4 was divergent with reduced infiltration and activation of immune cells in brain tumors. Additional therapies may be needed for effective antitumor immune response against melanoma brain metastases.